Analysis of The Effects of Bad Weather on The Use of Dynamic Positioning to Support Offshore Operations of AHTS Vessels. OPS AORA - Widar Bayu Wantoro; Mohammad Haris Irsyam Sah; Susanto, Susanto; Marselia, Marselia; Erwin Sutantyo (Dinamika Bahari, 2025)
AHTS vessels are tasked with performing heavy-duty operations such as towing and deploying anchors, which are critical steps in the installation and relocation of platforms at designated locations. The Dynamic Positioning System (DPS) consists of several separate modules, each performing its specific function, and collectively counteracting environmental disturbances such as wind, currents, and waves. The operation of the dynamic positioning system is carried out by the captain, assisted by ship officers who hold DPO certification. As the DP system operator, the DPO is responsible for monitoring, evaluating, and controlling the performance of the DP system to ensure the vessel remains stable and in the correct position during operations in waters with adverse weather conditions. This study was conducted to investigate Dynamic Positioning (DP) on the AHTS vessel OPS AORA, which was operating suboptimally. The adverse weather conditions caused the vessel to lose its position. This incident disrupted the vessel's operations during DP operations at the Borr Thor offshore rig in the Bukit Tua Field of Petronas. The study was conducted using a qualitative case study approach. The impact of adverse weather conditions on the Dynamic Positioning (DP) system in the context of offshore AHTS vessel operations was explored through interviews with experienced masters and officers. The research findings revealed that sensor and navigation malfunctions, reduced thruster efficiency, and decreased vessel stability caused the DP system to lose accuracy, potentially leading to position failure and increased accident risks. The implementation of technical and procedural mitigation strategies, such as sensor redundancy, real-time monitoring of sea conditions, and enhancing operator competence, can effectively control the negative impacts of adverse weather conditions.